Simulation Model of PV System Function in Stand-Alone Mode for Grid Blackout Area - Bibhu Prasad Ganthia; R. Dharmaprakash; Tushar Choudhary; T. Vijay Muni; Essam A. Al-Ammar; A. H. Seikh; M. H. Siddique; Abdi Diriba (International Journal of Photoenergy)
PV systems are frequently used in a stand-alone configuration. In a solar PV-based energy-producing system, power fluctuation is a natural occurrence. Alternative sources of energy, including such hybrid grid-tied or energy storage systems, could be discovered when solar PV systems run off-grid to satisfy regional power demands for reliable power supply. This research uses an unusual PV system that can function in both grid-connected and stand-alone states to propose an efficient approach for the power generation challenge in the residential segment. A block of storage battery with sufficient dimensions is included in the system to make sure the constant power supply of such a residential building with an average electricity demand of 10 kWh. An atypical 3.2 kWp PV system and a 19.2 kWh storage battery brick was determined to be capable of meeting the house’s whole daily energy requirements, as well as the defined electrical shutdown times, to simulate the system, which took into account the day load profile, network cutoff times, and monthly radiation from the sun. The collected simulation results showed that during 9 months of each year, the generated PV energy surpasses the load needs, resulting in a maximum battery state-of-charge (SOC) in the range of 74-85%. The generated PV energy is an approximately proportional requirement as during 3 months of minimum solar irradiance (Dec-Feb), whereas the sequence’s SOC differs between 40 and 49%, demonstrating the validity of the proposed photovoltaic system. In January and July, the PV service’s daily energy produced ranges between 2.6 and 5.4 kWh/kWp, corresponding to a conversion efficiency of 90% and 66.25%, correspondingly.